2010
DOI: 10.1007/s10393-010-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

A Reflective Lens: Applying Critical Systems Thinking and Visual Methods to Ecohealth Research

Abstract: Critical systems methodology has been advocated as an effective and ethical way to engage with the uncertainty and conflicting values common to ecohealth problems. We use two contrasting case studies, coral reef management in the Philippines and national park management in Australia, to illustrate the value of critical systems approaches in exploring how people respond to environmental threats to their physical and spiritual well-being. In both cases, we used visual methods--participatory modeling and rich pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In particular, the findings have underlined the importance of the appreciation of nuance, effective communication, and co-ordinated action in accelerating change. Previous research had demonstrated the utility of CSH as a framework for uncovering practical recommendations for problems concerning the environment and sustainability (Cleland and Wyborn 2010;Klocker Larsen 2011;Lyons-White et al 2022;Simbolon 2017). We contribute to this body of research by proposing a transparent and accessible approach to conducting reflective interviews based on the CSH framework to explore a novel issue in Scottish agriculture.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, the findings have underlined the importance of the appreciation of nuance, effective communication, and co-ordinated action in accelerating change. Previous research had demonstrated the utility of CSH as a framework for uncovering practical recommendations for problems concerning the environment and sustainability (Cleland and Wyborn 2010;Klocker Larsen 2011;Lyons-White et al 2022;Simbolon 2017). We contribute to this body of research by proposing a transparent and accessible approach to conducting reflective interviews based on the CSH framework to explore a novel issue in Scottish agriculture.…”
Section: Discussionmentioning
confidence: 97%
“…One of the benefits of this approach is the ease with which it can be applied -interviews need not adhere to CSH's boundary questions, and the research output is not dependent on the effectiveness with which boundary critique is practiced during data collection. Other applications of CSH are more closely aligned with Ulrich's design, in that CSH features more extensively in the research design, guiding data collection from the outset (Cleland and Wyborn 2010;Kish et al 2021;Klocker Larsen 2011;Venter and Goede 2018). Our research follows more closely this second approach, adopting CSH as a framework for guiding inquiry and reflection (Ulrich and Reynolds 2010), while also incorporating features of a more pragmatic orientation.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar to Cleland and Wyborn (2010) this research borrows from both critical systems thinking [Ulrich's critical systems heuristics (CSH) (Ulrich 1983)] and soft systems methodology (SSM) Checkland and Scholes 2005). SSM provided the core method to explore the situation and model relevant systems of interest, while CSH provided a means to compare models and explore judgements in the design of system boundaries.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Angell et al [28] reported that a draw-and-tell approach enables participation, in which users are given time and space to think, and facilitates the building of central ideas or key themes. Cleland and Wyborn [29] showed that drawings in participatory studies encourage people to demonstrate the details of the values, behaviors, and abstract concepts that they are projecting to the world. The preference toward participating in participatory environmentally friendly message design, degree of ease in drawing the intended message representations, and the degree of agreement with using a drawing method to illustrate the intended message representations were dependent variables of this study.…”
Section: Introductionmentioning
confidence: 99%